PENGARUH HIPERSEKURITISASI DAN PRAKTIK KEAMANAN SIBER HARIAN TERHADAP KEPATUHAN MAHASISWA DALAM MENGHADAPI ANCAMAN DIGITAL - Algi Fahrizal; Muh Fikri Ainul Yakin; Hajar Dewantara; Andi Naila Quin Azisah Alisyahbana; Diarra Salim (Jurnal Pendidikan Terapan, 2025)
While advances in information technology have many benefits, they also increase cybersecurity risks, especially for students. The purpose of this study was to see how hypersecuritization and daily cybersecurity practices affect students' compliance with digital security policies. This descriptive quantitative study involved 94 students from various majors, and data was collected through an online survey that used a five-level Likert scale. The results showed that hypersecuritization had a mean score of 4.04, which indicates that people are very wary of cyber threats. The mean score of 4.01 for daily cybersecurity practices indicates positive behaviors such as the use of two-factor authentication and device updates. Although more flexible policies are needed, the mean score of 3.86 indicates a fairly high acceptance of cybersecurity policies. This study found that to improve students' knowledge and compliance about cybersecurity, education-based methods and more inclusive policies are needed.